Optimizing Surgical Techniques in General and Orthopedic Surgery A Comparative Study on Patient Recovery and Complications - Abdul Waheed, Tanveer Sadiq Ch, Mohammad Aslam Mengal, Tauseef Raza, Saifullah Brohi, Muhammad Arif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical advancements have significantly improved patient outcomes by reducing complications, hospital stays, and recovery time. However, in Pakistan, healthcare infrastructure varies across regions, necessitating the optimization of surgical techniques for enhanced efficiency and patient care. Despite global trends favoring minimally invasive procedures, conventional surgical methods remain prevalent due to limited access to technology, gaps in surgeon training, and economic constraints. Aims and Objectives: This study aimed to compare conventional and advanced surgical techniques in general and orthopedic surgery, assessing their impact on patient recovery, postoperative complications, and healthcare costs in tertiary care hospitals in Pakistan. The objective was to evaluate the clinical and economic benefits of minimally invasive techniques and provide evidence-based recommendations for optimizing surgical care. Methods: A comparative study was conducted in multiple tertiary care hospitals in Pakistan, involving 150 patients equally divided into conventional and advanced surgical groups. Patients were followed up for six months postoperatively. Key parameters assessed included hospital stay duration, postoperative complications, return to normal activity, readmission rates, revision surgery rates, and surgical costs. Statistical analysis was performed using SPSS version 26, with a significance threshold of p < 0.05. Results: Patients in the advanced surgery group had a significantly shorter hospital stay (4.2 vs. 7.5 days, P < 0.001), faster recovery (5.6 vs. 8.2 weeks, P < 0.001), and fewer postoperative infections (5.3% vs. 16.0%, P = 0.03). Additionally, the advanced group had lower readmission (6.7% vs. 13.3%) and revision surgery rates (4.0% vs. 10.7%). Although the cost of advanced surgery was higher (PKR 750,000 vs. PKR 500,000, P < 0.001), the improved outcomes suggest potential long-term cost-effectiveness. Conclusion: Minimally invasive surgical techniques in Pakistan have demonstrated superior patient recovery, reduced complications, and improved surgical efficiency. Despite higher initial costs, their long-term benefits justify wider adoption through enhanced training programs, technological investment, and healthcare policy support. Keywords: Surgical techniques, minimally invasive surgery, general surgery, orthopedic surgery, Pakistan, patient recovery, postoperative complications, cost-effectiveness, and healthcare optimization.